Romantic Relationship Suami Istri Beda Usia (Studi Kasus di Desa Sukasari Kecamatan Kaduhejo Kabupaten Pandeglang) - Sutantri, Putri; Nursih, Isti; Winangsih, Rahmi (LUGAS Jurnal Komunikasi, 2023)
Interpersonal communication in the household between husband and wife is the most important thing to build a romantic relationship because not all couples can have a good relationship. The purpose of this study was to determine the reciprocity carried out by husband and wife of different ages in the household, to determine the emotionality of husband and wife of different ages in the household, and to determine the eroticism of husband and wife of different ages in the household. The subjects in this study were married couples with an age difference (13-20 years). The theory used was the Social Penetration Theory popularized by Irwin Altman and Dalmas Taylor (1973). This research uses descriptive qualitative method with constructivist paradigm. The data collection technique uses in-depth interviews. The results of this study indicate that the age difference between husband and wife in Sukasari Village, Kaduhejo District, Pandeglang Regency, does reciprocity that occurs in the household, there is good treatment for partners, mutual understanding and acceptance of partners, of course there is communication such as being open to each other, providing mutual support, having good empathy. high level, positive thinking to each other to trust each other, and equality in the household. The emotions that occur between three married couples in their household experience high emotions, such as anger, fear, joy, and calm emotions. Then the level of eroticism or sexuality of the informants in the households of husband and wife with different ages has a different sexual level for each partner due to the age factor, then sex becomes a need and happiness in the relationship.